Interplay of Polarity and Confinement in Asymmetric Catalysis with Chiral Rh Diene Complexes in Microemulsions. Issue 68 (23rd November 2021) - Kirchhof, Manuel; Abitaev, Karina; Abouhaileh, Abdulwahab; Gugeler, Katrin; Frey, Wolfgang; Zens, Anna; Kästner, Johannes; Sottmann, Thomas; Laschat, Sabine
Abstract: Microemulsions provide a unique opportunity to tailor the polarity and liquid confinement in asymmetric catalysis via nanoscale polar and nonpolar domains separated by a surfactant film. For chiral diene Rh complexes, the influence of counterion and surfactant film on the catalytic activity and enantioselectivity remained elusive. To explore this issue chiral norbornadiene Rh(X) complexes (X=OTf, OTs, OAc, PO2 F2 ) were synthesized and characterized by X‐ray crystallography and theoretical calculations. These complexes were used in Rh‐catalyzed 1, 2‐additions of phenylboroxine to N‐ tosylimine in microemulsions stabilized either exclusively by n ‐octyl‐ β ‐D‐glucopyranoside (C8 G1 ) or a C8 G1 ‐film doped with anionic or cationic surfactants (AOT, SDS and DTAB). The Rh(OAc) complex showed the largest dependence on the composition of the microemulsion, yielding up to 59 % (90 %ee) for the surfactant film doped with 5 wt% of AOT as compared to 52 % (58 %ee) for neat C8 G1 at constant surfactant concentration. Larger domains, determined by SAXS analysis, enabled further increase in yield and selectivity while the reaction rate almost remained constant according to kinetic studies. Abstract : Doping the nanoscale confinement of microemulsions with cationic surfactants improves yield and chirality transfer in the Rh‐catalyzed nucleophile additions.